Interaction of Hawking radiation with static sources outside a Schwarzschild black hole - Higuchi, Atsushi; Matsas, George E. A. [UNESP]; Sudarsky, Daniel (American Physical Society (APS), 1998)
We show that the response rate of (i) a static source interacting with Hawking radiation of a massless scalar field in Schwarzschild spacetime (with the Unruh vacuum) and that of (ii) a uniformly accelerated source with the same proper acceleration in Minkowski spacetime (with the Minkowski vacuum) are equal. We show that this equality will not hold if the Unruh vacuum is replaced by the Hartle-Hawking vacuum. It is verified that the source responds to the Hawking radiation near the horizon as if it were at rest in a thermal bath in Minkowski spacetime with the same temperature. It is also verified that the response rate in the Hartle-Hawking vacuum approaches that in Minkowski spacetime with the same temperature far away from the black hole. Finally, we compare our results with others in the literature.